Theoretical Investigation of Photoisomerization Mechanisms of N-Salicilydenemethylfurylamine (SMFA) (Journal of Atomic and Molecular Sciences, 2015)
TExcited state reaction coordinates and the consequent energy profiles ofa new Schiff base, N-salicilydenemethylfurylamine (SMFA), have been investigatedwith the MP2 and CASSCF method. The potential energy profiles of the ground andthe lowest excited singlet state are calculated. The excited state potential energy profileshows a small barrier in the LIIC pathway of dissociation along the O-H stretchingcoordinate. This work suggests that there are two pathways in the photochemical reactionof SMFA. In one pathway, the photochemical product is the enol-type minimum.In the other pathway, the ESIPT reaction is observed and a excited state stationarystructure is reached. The trans-keto and cis-keto type structures will be obtained fromphotoexcitation of the enol isomer. Two conical intersections between the ground andexcited states act as the gates for nonadiabatic decay to the ground state.